A Foreigner's Cinematic Dream of Japan : Representational Politics and Shadows of War in the Japanese-German Coproduction New Earth (1937) /: Representational Politics and Shadows of War in the Japanese-German Coproduction New Earth (1937). (2020) - Haukamp, Iris
No abstract available